1996
DOI: 10.1002/zaac.19966220118
|View full text |Cite
|
Sign up to set email alerts
|

Supraleitung in Seltenerdmetall‐Carbidhalogeniden des Typs SE2X2C2

Abstract: Die metallischen Eigenschaften der Carbidhalogenide Y2X2C2 beruhen auf YC‐Kovalenz. Die Supraleitung der Verbindungen wird auf paarweise Attraktion von Leitungselektronen durch C2‐π*‐Zustände an der Fermikante zurückgeführt. Diese Hypothese wird experimentell und mit Bandstrukturrechnungen verfolgt. Neutronenbeugung am Pulver ergibt d(CC) = 128(1) pm für Y2Br2C2. Röntgeneinkristalluntersuchungen an Y2Br2C2 und Y2I1,5Br0,5C2 zeigen eine charakteristische Änderung der Koordination für die C2‐Gruppe. Die system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
1
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 40 publications
7
54
1
7
Order By: Relevance
“…The same structures have been reported for ScCl, YCl, and many of the lanthanide chlorides and bromides¸nX (X"Cl, Br), although it was subsequently found that all the monohalides of the trivalent elements are actually ternary phases¸nXH V stabilized by hydrogen (27,28). The insertion of the nitrogen atoms in all of the tetrahedral holes between the double metal layers of ZrCl and ZrBr will give the -ZrNCl (SmSItype) and -ZrNI (YOF-type) structures, respectively, whereas the "lling of the octahedral interstitial voids of nXH V with C pairs will result in the superconducting carbide halides¸n C X (¸n"La, Y, Lu; X"Br, I) which also crystallize in two polymorphs: the 1 s form with a periodicity A c B (based on the parent ZrCl structure), and the 3 s form with a periodicity A c B"C b A"B a C (derived from the ZrBr structure) (X"A, B, C; C " a, b, c;¸n" , , ) (29). In fact, -ZrNCl, ZrCl, -ZrNI, and ZrBr crystallize in the same space group with similar unit cells.…”
Section: Related Layer Structuresmentioning
confidence: 99%
“…The same structures have been reported for ScCl, YCl, and many of the lanthanide chlorides and bromides¸nX (X"Cl, Br), although it was subsequently found that all the monohalides of the trivalent elements are actually ternary phases¸nXH V stabilized by hydrogen (27,28). The insertion of the nitrogen atoms in all of the tetrahedral holes between the double metal layers of ZrCl and ZrBr will give the -ZrNCl (SmSItype) and -ZrNI (YOF-type) structures, respectively, whereas the "lling of the octahedral interstitial voids of nXH V with C pairs will result in the superconducting carbide halides¸n C X (¸n"La, Y, Lu; X"Br, I) which also crystallize in two polymorphs: the 1 s form with a periodicity A c B (based on the parent ZrCl structure), and the 3 s form with a periodicity A c B"C b A"B a C (derived from the ZrBr structure) (X"A, B, C; C " a, b, c;¸n" , , ) (29). In fact, -ZrNCl, ZrCl, -ZrNI, and ZrBr crystallize in the same space group with similar unit cells.…”
Section: Related Layer Structuresmentioning
confidence: 99%
“…In older and recent reports the monohalides of zirconium [83][84][85] and the rare-earth metal halide carbides [86,87], especially Y 2 Br 2 C 2 , were mentioned as prominent examples for related crystal structures. Due to their similar stacking sequences of metal layers and halide anions it is near at hand to compare these compounds with their MNX relatives, particularly since lithium intercalation into YClH x (ZrBr-type structure) succeeded [88].…”
Section: Compounds With Structures Related To B-mnxmentioning
confidence: 99%
“…Mit Z = C sind Methanide (C 4-), wie in La 2 CCl [12], oder Ethenide (C 2 4-) in Y 2 (C 2 )Br 2 [13] und den Wellenstrukturen von La 6 (C 2 ) 3 Cl 4 [14] bis La 36 (C 2 ) 18 Cl 23 [15], sowie in gewinkelter Anordnung bei Gd 6 Cl 5 C 3 [16] und Gd 4 C 2 X 3 [17] bekannt. Die Halogenatome befinden sich zwischen den Ln 6 …”
Section: Introductionunclassified